Identification of unique microRNA expression patterns in bone marrow hematopoietic stem and progenitor cells after hemorrhagic shock and multiple injuries in young and old adult mice. Issue 4 (October 2021) - Darden, Dijoia B.; Mira, Juan C.; Lopez, Maria-Cecilia; Stortz, Julie A.; Fenner, Brittany P.; Kelly, Lauren S.; Nacionales, Dina C.; Budharaju, Ashrita; Loftus, Tyler J.; Baker, Henry V.; Moore, Frederick A.; Brakenridge, Scott C.; et al.
Abstract : BACKGROUND: After severe trauma, the older host experiences more dysfunctional hematopoiesis of bone marrow (BM) hematopoietic stem and progenitor cells (HSPCs), and dysfunctional differentiation of circulating myeloid cells into effective innate immune cells. Our main objective was to compare BM HSPC microRNA (miR) responses of old and young mice in a clinically relevant model of severe trauma and shock. METHODS: C57BL/6 adult male mice aged 8 to 12 weeks (young) and 18 to 24 months (old) underwent multiple injuries and hemorrhagic shock (polytrauma [PT]) that engenders the equivalent of major trauma (Injury Severity Score, >15). Pseudomonas pneumonia (PNA) was induced in some young and old adult mice 24 hours after PT. MicroRNA expression patterns were determined from lineage-negative enriched BM HSPCs isolated from PT and PT-PNA mice at 24 and 48 hours postinjury, respectively. Genome-wide expression and pathway analyses were also performed on bronchoalveolar lavage (BAL) leukocytes from both mouse cohorts. RESULTS: MicroRNA expression significantly differed among all experimental conditions ( p < 0.05), except for old-naive versus old-injured (PT or PT-PNA) mice, suggesting an inability of old mice to mount a robust early miR response to severe shock and injury. In addition, young adult mice had significantly more leukocytes obtained from their BAL, and there were greater numbers of polymorphonuclear cells compared with old mice (59.8% vs. 2.2%, p = 0.0069). Despite increased gene expression changes, BAL leukocytes from old mice demonstrated a more dysfunctional transcriptomic response to PT-PNA than young adult murine BAL leukocytes, as reflected in predicted upstream functional pathway analysis. CONCLUSION: The miR expression pattern in BM HSPCs after PT (+/−PNA) is dissimilar in old versus young adult mice. In the acute postinjury phase, old adult mice are unable to mount a robust miR HSPC response. Hematopoietic stem and progenitor cell miR expression in old PT mice reflects a diminished functional status and a blunted capacity for terminal differentiation of myeloid cells. Abstract : Supplemental digital content is available in the text.